Muscle‐ultrasound evaluation in healthy pediatric subjects: Age‐related normative data. Issue 2 (15th June 2018) - Lori, Silvia; Lolli, Francesco; Molesti, Elisabetta; Bastianelli, Maria; Gabbanini, Simonetta; Saia, Valentina; Trapani, Sara; Marinoni, Marinella
ABSTRACT: Introduction : The muscle ultrasound examination (MUS) is a noninvasive and inexpensive technique for evaluating neuromyopathies. Standardized MUS normative data are incomplete in pediatric subjects. Methods : We performed a MUS study with 120 healthy children (59 males; mean age, 10.44 years; age range, 2–16 years). We measured the width and the echogenicity bilaterally in the following muscles: biceps brachii and brachialis, brachioradialis, forearm‐flexors, rectus femoris and vastus intermedius, tibialis anterior, extensor hallucis longus, lateral and medial gastrocnemius. Results : The muscle thickness increased with age for all muscles. Confidence limits were set for each age group muscle width. Echogenicity increased with age only in some muscles. Discussions : Our MUS study provides new data on physiological muscle structural changes in healthy children to address the limited available references in this age group. Muscle Nerve 58 : 245–250, 2018